การอรรถาธิบายความหมาย (الأرض) ในอายะฮฺที่ 4 จากซูเราะฮฺอัลอิรออฺ : ศึกษาแนวทางการก่อความเสียหายของบนีอิสราเอลในแผ่นดิน - Solhan, Muhammaddawood (Al-HIKMAH Journal, 2021)
This paper aims to study The Interpretation Surat Al-Israa Ayat: 4 (الأرض). The objectives are 1) In order to prove how this Bani-Israel Study guidelines to do mischief on the earth. and, 2) to study the methodology of the past Muslims scholars or Interpreters of the Quran and, 3) to study the methodology of the contemporary Muslims scholars or Interpreters of the Quran . The study will be at the 4 verse, surat Al-Isra’a: ((وقضينا إلى بني إسرائيل في الكتاب لتفسدن في الأرض مرتين ولتعلن علوا كبيرا) that: And We gave (Clear) Warning to the Children of Israel in the Book, that twice would they do mischief on the earth and be elated with mighty arrogance (and twice would they be punished) And We gave (Clear) Warning to the Children of Israel in the Book, that twice would they do mischief on the earth and be elated with mighty arrogance (and twice would they be punished)”. The study found that 1) The course of the destruction of Bani Israel on the earth will cover the whole world, Not just somewhere or in only one part. 2) The methodology of Muslims scholars or Interpreters of the Quran in the past: Al-Thabariy - Died in Hijri year 310 (Al-Thabariy, Muhammad bin Jarir. 2003 : 17/354):: on the earth (في الأرض) Referring to the city of God Without specifying that somewhere, that He didn't say clearly. But in the explanation, the verse is within limits which can be understood as Jerusalem And Al-Aqsa Mosque. Al-Baghawiy - Died in Hijri year 510 (Al-Baghawiy, Al-husain Ibn Mas’uuwd. 2002 : 736): The course of the destruction of Bani Israel on the earth (في الأرض) as Jerusalem And Al-Aqsa Mosque. Al- Raziy - Died in Hijri year 604 (Al- Raziy, Muhammad.1981 : 15/156): on the earth (في الأرض) as Egypt. Al-Qurtubiy - Died in Hijri year 671 (Al-Qurtubiy, Muhammad bin Ahmad Al-’Ansariy. 2002 : 5 : 555) : The course of the destruction of Bani Israel,that Is a violation of the Torah's teachings. and on the earth (في الأرض) as Jerusalem And Al-Aqsa Mosque.